1999
DOI: 10.1590/s1415-47571999000300018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and population structure in loci related to milk production traits in native Argentine Creole and commercial Argentine Holstein cattle

Abstract: Many cattle breeds have been subjected to high selection pressure for production traits. Consequently, population genetic structure and allelic distribution could differ in breeds under high selection pressure compared to unselected breeds. Analysis of <FONT FACE="Symbol">k</font>-casein, <FONT FACE="Symbol">a</font>S1-casein and prolactin gene frequencies was made for Argentine Creole (AC) and Argentine Holstein (AH) cattle herds. The calculated FST values measured the degree of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…Kappa casein (CSN3) is the most extensively studied milk protein in cattle which showed two predominant DNA genotypes AB and AA in present study with 0.16 and 0.82 frequencies respectively (Figure 2), two out of 120 animals studied were with CC genotype (frequency = 0.02). Allele A was more frequent in Sahiwal cattle than allele B, that is, 0.92 and 0.08, respectively (Figure 3) corroborating several findings (Ng-Kwai-Hang et al, 1984;Pinder et al, 1994;Kemenes et al, 1999, Golijow et al, 1999Lara et al, 2002;Yasemin and Cengiz, 2006;Alipanah et al, 2008) that observed this in B. indicus and B. taurus . The genotyping results are also similar to earlier studies reported for Korean native cattle, Japanese brown, Angus, Hereford, Charolais and Holstein cows by Hung et al (1995Hung et al ( , 1998.…”
Section: Allele and Genotype Frequency Distributionsupporting
confidence: 84%
See 1 more Smart Citation
“…Kappa casein (CSN3) is the most extensively studied milk protein in cattle which showed two predominant DNA genotypes AB and AA in present study with 0.16 and 0.82 frequencies respectively (Figure 2), two out of 120 animals studied were with CC genotype (frequency = 0.02). Allele A was more frequent in Sahiwal cattle than allele B, that is, 0.92 and 0.08, respectively (Figure 3) corroborating several findings (Ng-Kwai-Hang et al, 1984;Pinder et al, 1994;Kemenes et al, 1999, Golijow et al, 1999Lara et al, 2002;Yasemin and Cengiz, 2006;Alipanah et al, 2008) that observed this in B. indicus and B. taurus . The genotyping results are also similar to earlier studies reported for Korean native cattle, Japanese brown, Angus, Hereford, Charolais and Holstein cows by Hung et al (1995Hung et al ( , 1998.…”
Section: Allele and Genotype Frequency Distributionsupporting
confidence: 84%
“…Most common allelic forms observed in different breeds are B and C. The present data agree with previous reports (Aschaffenburg, 1968;Aschaffenburg et al, 1968) that predominance of the alpha s1 casein C allele in the Sahiwal cattle (B. indicus) contrasts with the high frequency of the alpha s1 casein B allele (90 to 95%) in Bos taurus breeds. A frequency close to 0.9 was reported for the C variant in B. indicus (Ivana and Marco, 1997) and Bos grunniens (Eigel et al, 1984) while in B. taurus its frequency ranges from 0.2 to 0.4 (Baker and Manwell, 1980;Baranyi, 1992;Golijow et al, 1999;Yasemin and Cengiz, 2006). This asymmetric distribution in B. indicus breeds and European cattle breed has been explained by the different processes of domestication to which these animals were submitted (Grosclaude et al, 1974).…”
Section: Allele and Genotype Frequency Distributionmentioning
confidence: 72%
“…The polymorphism of milk protein is of particular interest due to its possible role in selection and genetic classification of different animal breeds (Del Lama and Zago ; Golijow et al . ; Kemenes et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be due to the number of animals used in both these studies. Golijow et al. (1999) found a low frequency of allele B in Argentine Holstein (0.344) and Argentine Creole (0.353) as compared to allele A.…”
Section: Resultsmentioning
confidence: 83%